Islamic Religious Education in Elderly Families in Tangkahan Village, Medan Labuhan Subdistrict, Medan City - Nafisa Nur Azza; Abdul Fattah Nasution (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The intent of this research is to investigate the execution of Islamic religious education in senior households residing in Tangkahan Village, Medan Labuhan District, Medan City. This research employs a qualitative methodology with a case study approach to investigate several facets of Islamic religious education for the elderly. It examines both the elements that facilitate and impede this education, as well as the involvement of families and religious leaders in the process. The data was gathered via participatory observation, in-depth interviews, and documentation, and then analysed using theme analysis approaches. The research findings suggest that Islamic religious education for the elderly in Tangkahan Village is conducted via regular activities, including religious lectures and Quranic studies. The primary contributing aspects are the elderly's strong motivation and the active endorsement from their family and religious leaders. Nevertheless, this research also identified some challenges, including a deterioration in the physical and mental health of the elderly and a wide range of religious educational backgrounds. Ultimately, the consistent provision of Islamic religious education is crucial for enhancing the spiritual well-being of the old. To achieve effective and meaningful education, it is essential to foster joint endeavours among the elderly, their families, and the surrounding environment.